2022
DOI: 10.1111/iej.13799
|View full text |Cite
|
Sign up to set email alerts
|

Use of scaffolds and regenerative materials for the treatment of immature necrotic permanent teeth with periapical lesion: Umbrella review

Abstract: Background: Current treatment of immature necrotic permanent teeth with a periapical lesion is regenerative endodontics, which is based on tissue engineering under the triade of stem cells, scaffolds and bioactive molecules.Objectives: This Umbrella Review was aimed to evaluate the success of scaffold and regenerative materials used for the treatment of these teeth, in terms of apical closure, tooth length increase, widening of root canal walls, tissue vitality and periapical lesion repair.Methods: An extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The basic principles of GER include removal of necrotic tissues, minimal or no root canal instrumentation, copious irrigation with NaOCl and control of infection with or without intracanal medication similar to apexification treatment 83 . GER is generally performed by inducing apical bleeding to form a blood clot in the root canal and placing a CSC on the clot as a coronal barrier 84 . CSCs are preferred in this treatment as they provide a good coronal seal, have antibacterial effects due to high pH and Ca(OH) 2 release, and allow hydroxyapatite formation in contact with tissue fluids 84 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The basic principles of GER include removal of necrotic tissues, minimal or no root canal instrumentation, copious irrigation with NaOCl and control of infection with or without intracanal medication similar to apexification treatment 83 . GER is generally performed by inducing apical bleeding to form a blood clot in the root canal and placing a CSC on the clot as a coronal barrier 84 . CSCs are preferred in this treatment as they provide a good coronal seal, have antibacterial effects due to high pH and Ca(OH) 2 release, and allow hydroxyapatite formation in contact with tissue fluids 84 .…”
Section: Introductionmentioning
confidence: 99%
“…GER is generally performed by inducing apical bleeding to form a blood clot in the root canal and placing a CSC on the clot as a coronal barrier 84 . CSCs are preferred in this treatment as they provide a good coronal seal, have antibacterial effects due to high pH and Ca(OH) 2 release, and allow hydroxyapatite formation in contact with tissue fluids 84 . During primary dentinogenesis, growth factors and bioactive molecules are secreted by odontoblasts and are incorporated within the dentine extracellular matrix 85 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional BC maturogenesis approaches remain poorly studied. In addition, previous studies addressing this topic have shown inconsistent results and methodological flaws ( 9 ). Consequently, this study aims to perform a systematic literature review to evaluate the effectiveness of platelet concentrates (PRP and PRF) compared with BC as scaffolds for maturogenesis in patients with immature permanent teeth with or without AP.…”
Section: Introductionmentioning
confidence: 99%